Does Religion Matter? Understanding Religion Subject for Formal Education - Riza Adrian Soedardi (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
In modern education, religion becomes a study that is not prioritized because it is transcendental. Religion subject in formal education involves ambiguity in search of learning purposes. Some countries choose to return religious studies as an option rather than a mandatory subject. This study attempts to examine the importance of religion subject in formal education. The method employs literature reviews from research reports of the model of religion subject in particular countries thus these are compared with the religion subject model in Indonesia. The results show that developed countries reform religion subjects as an optional subject, while Indonesia might recognize religion subjects in formal education even though it factually does not indicate suitability for configuring students' characters.